The Efficiency of Government Health Expenditure in ASEAN Countries - Raden Ayu Adinda Shafira Najmah; Estro Dariatno Sihaloho (Economics Development Analysis Journal, 2025)
Inefficiencies in health expenditure result in an estimated 1–1.4% of global Gross Domestic Product (GDP) being wasted across various regions, presenting a significant challenge for countries striving to optimize healthcare spending. This study aims to assess the efficiency of government health expenditure in six ASEAN countries with the lowest per capita government health spending, using the Data Envelopment Analysis (DEA) method. In addition, Tobit regression is employed to identify factors that influence the efficiency of government health expenditure. The results indicate that most countries have not achieved maximum efficiency scores over the years, underscoring the need for improved budget management and reforms in health policy implementation. The Tobit regression analysis reveals that economic growth, urbanization rate, and the proportion of government health expenditure in current health expenditure have a positive and significant effect on efficiency scores. This suggests that increased public investment and urban development contribute to improved efficiency in healthcare spending. Conversely, total carbon emissions have a negative impact on efficiency, emphasizing the influence of environmental factors on health system performance.